Model'no-tselevoi sposob postroeniya sportivnoi podgotovki vysokokvalifitsirovannykh sportsmenov v zimnikh tsiklicheskikh vidakh sporta (stat'ya vtoraya) - Batalov, A. G. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The author of this paper considers the available opportunities and problems in the realization of the model-purpose approach to construction of speedskiers sports preparation. - precondition of modeling of competitive activity of speedskiers; - opportunity of the settlement forecasting the sport-technical result in ski races; - modeling of the external individual parameters of competitive activity; - modeling of the internal parameters of competitive activity.